Evolution of discrete local levels into an impurity band in solidified inert gas solution: Classical Cryocrystals - Kosevich, A.M.; Feodosyev, S.B.; Gospodarev, I.A.; Grishaev, V.I.; Kotlyar, O.V.; Kruglov, V.O.; Manzhelii, E.V.; Syrkin, E.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The density of states g(w)of disordered solutions of solidified inert gases have been calculated using the Jacobian matrix method. The transformation of a discrete vibrational level into an impurity zone at a growing concentration of light impurity atoms has been investigated. It is shown that a 1–10% change in theimpurity concentration leads to smearing the local discrete level into an impurity band. As this occurs, additional resonance levels appear which carry important information about the impurity–impurity and impurity–basic lattice force interactions in such solutions.